2019
DOI: 10.1101/767574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atoh1 is repurposed from neuronal to hair cell determinant by Gfi1 acting as a coactivator without redistribution of its genomic binding sites

Abstract: Although the lineage-determining ability of transcription factors is often modulated according to cellular context, the mechanisms by which such switching occurs are not well known. Using a transcriptional programming model, we found that Atoh1 is repurposed from a neuronal to an inner ear hair cell (HC) determinant by the combined activities of Gfi1 and Pou4f3. In this process, Atoh1 maintains its regulation of neuronal genes but gains ability to regulate HC genes. Pou4f3 enables Atoh1 access to genomic locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…S5A), suggesting that the derepression of a neuronal differentiation program in Pou4f3 mutants is due to the loss of an active inhibitory mechanism. Evidence suggests that this active inhibitory mechanism in wild-type hair cells may be mediated by the transcriptional repressor GFI1 (63)(64)(65), which we show is also one of the POU4F3-dependent ATOH1 targets in hair cells (Fig. 2D and Dataset S1).…”
Section: Discussionmentioning
confidence: 70%
“…S5A), suggesting that the derepression of a neuronal differentiation program in Pou4f3 mutants is due to the loss of an active inhibitory mechanism. Evidence suggests that this active inhibitory mechanism in wild-type hair cells may be mediated by the transcriptional repressor GFI1 (63)(64)(65), which we show is also one of the POU4F3-dependent ATOH1 targets in hair cells (Fig. 2D and Dataset S1).…”
Section: Discussionmentioning
confidence: 70%
“…The stratification of TF binding regions according to multiple functional and biological criteria can reveal subgroups of enriched E-boxes. Additional motifs of other transcription factors can also be enriched in the bound regions, indicating putative cooperative binding [95,98,162,184,189,[256][257][258][259][260][261]. Finding fixed spacing patterns between the motifs [182] and/or leveraging ChIP-seq data of the co-enriched transcription factors and finding overlapping binding sites provides further validation of these inferred co-binding events [95,256].…”
Section: Chip-seqmentioning
confidence: 89%
“…Gfi1 has a SNAG transcriptional repressor domain on the N-terminus 48 . Atoh1 is both necessary and sufficient for neuronal differentiation in the brain and spinal cord 49 , 50 , and it has recently been suggested that Gfi1 acts to repress neuronal gene networks during HC differentiation 51 , 52 . Gfi1 function has been best characterized in the hematopoietic system, where it acts chiefly as a transcriptional repressor by recruiting and forming complexes with chromatin modifier proteins such as histone deacetylase (HDAC) 1–3, histone methyltransferase (G9a) and histone demethylase complex 53 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Senseless, the Drosophila orthologue of Gfi1 is able to interact physically with the Atoh1 orthologue atonal and enhance its transcriptional activity, and this physical interaction does not require the senseless protein to bind DNA 56 . Recent evidence in mouse embryonic stem cells suggests that Gfi1 protein also may bind to Atoh1 in regions of DNA that have no Gfi1 DNA binding motifs 51 , supporting this ‘Atoh1 co-factor’ function, but confirmation of this role will require better Gfi1 antibodies or mice carrying epitope-tagged Gfi1 protein. Obtaining SCs transfected with Gfi1 for RNA-seq, ATAC-seq and other sequencing assays may reveal genes with changed level of expression and suggest downstream effectors of this synergistic action of Atoh1 and Gfi1 .…”
Section: Discussionmentioning
confidence: 99%